Examining Correlates of Substance Use Treatment Needs for Adults Under Community Supervision - Graves, Brian D. (International journal of offender therapy and comparative criminology, 2025)
Substance use among criminal justice-involved adults is a significant concern for the rehabilitation and reintegration into their communities. Few have examined broader associations with substance use among those in probation or parole (community supervision) using an assessment of risks and needs with a representative sample. Using an assessment based on risk-need-responsivity principles, this research applies negative binomial analyses to examine sociodemographic, criminal, and other problem-area correlates of substance use risks and needs among a statewide dataset of adults in community supervision. Results indicated that mental health risk/need was the strongest predictor of substance use risk/need. Other risk areas, including criminal thinking, employment/education, and the presence of delinquent associates (peers/family) were associated with substance use. Implications highlight the ongoing call to develop integrated models of care that treat co-occurring disorders among adults in supervision. Additionally, diversion-oriented efforts that prevent adults with complex treatment needs from reentering the justice system are discussed.